PERSEPSI REMAJA TERHADAP BAHAYA COVID-19 - Natalia Ratna Yulianti; Anastasia Bella Widiyanta; Eka Wahyuningrum (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
Corona Virus Disease 2019 (Covid-19) caused by Sars-Cov-2 which was first discovered in the Wuhan area of China in 2019 and caused the pandemic is still not over. One of the factors that affect the length of the pandemic is the behavior of the people. In coffee shops/cafes, teenagers are still found gathering without keeping their distance and not wearing masks. Several studies have identified the level of knowledge or health literacy of adolescents as having an effect on this behavior, but there has been no further research on adolescents' perceptions of the dangers of COVID-19. The purpose of this study was to explore adolescents' perceptions of the dangers of COVID-19. This study uses a qualitative method with a phenomenological study design on five adolescents. Collecting data using in-depth interviews and analyzed using the Van Manen method. This study resulted in two themes, namely 1) At first it was normal, 2) Realizing dangerous diseases. The final statement that connects the two themes is “There is a change in perception of Covid-19.” Subsequent research can explore the role of parents in controlling Covid-19 prevention behavior in adolescents and design a web-based Covid-19 application for adolescents.